Multi-method biophysical analysis in discovery, identification, and in-depth characterization of surface‐active compounds - Zompra, Aikaterini A.; Chasapi, Styliani A.; Twigg, Matthew S.; Salek, Karina; Anestopoulos, Ioannis; Galanis, Alex; Pappa, Aglaia; Gutierrez, Tony; Banat, Ibrahim M.; Marchant, Roger; Euston, Stephen R.; Panayiotidis, Mihalis I.; et al. (Frontiers in Marine Science, 2022)
Synthetic surfactants are used in several industries, including manufacturing, pharmaceutical and cosmetic’s, food and feed, agriculture, petroleum and environmental remediation for their ability to adsorb to fluid and solid-water interfaces. However, their widespread use and their synthetic preparation through environmentally unfavorable processes counterbalances the value of this class of reagents. This fact has stimulated new efforts to exploit natural sources of surfactants, such as new classes of bacterial systems or manipulation of existing biological systems, that may produce, through an environmentally friendly process, new biodegradable surfactants and emulsifiers of high commercial value. A downside of microbial production of biobased chemicals such as these types of chemicals, is that their fermentation often yields crude materials consisting of several bioproducts with complex physical and chemical properties. Extraction, identification, and efficient characterization of biosurfactants from a crude mixture of biomolecules requires carefully designed, and detailed analytical processes using state-of-the-art methods. The purpose of this review article is to present the current state-of-the-art and future outlook on the various multidisciplinary biophysical methods applied in the discovery, extraction identification, and in-depth characterization of microbially-produced surface‐active compounds.